RNA Targeting in Inherited Neuromuscular Disorders: Novel Therapeutic Strategies to Counteract Mis-Splicing - Veronica Verdile; Gloria Guizzo; Gabriele Ferrante; Maria Paola Paronetto (Cells, 2021)
Neuromuscular disorders represent multifaceted abnormal conditions, with little or no cure, leading to patient deaths from complete muscle wasting and atrophy. Despite strong efforts in the past decades, development of effective treatments is still urgently needed. Advent of next-generation sequencing technologies has allowed identification of novel genes and mutations associated with neuromuscular pathologies, highlighting splicing defects as essential players. Deciphering the significance and relative contributions of defective RNA metabolism will be instrumental to address and counteract these malignancies. We review here recent progress on the role played by alternative splicing in ensuring functional neuromuscular junctions (NMJs), and its involvement in the pathogenesis of NMJ-related neuromuscular disorders, with particular emphasis on congenital myasthenic syndromes and muscular dystrophies. We will also discuss novel strategies based on oligonucleotides designed to bind their cognate sequences in the RNA or targeting intermediary of mRNA metabolism. These efforts resulted in several chemical classes of RNA molecules that have recently proven to be clinically effective, more potent and better tolerated than previous strategies.